Proteolysis dysfunction in the process of aging and age-related diseases - Frankowska, Natalia; Lisowska, Katarzyna; Witkowski, Jacek M. (Frontiers in Aging, 2022)
In this review, we discuss in detail the most relevant proteolytic systems that together with chaperones contribute to creating the proteostasis network that is kept in dynamic balance to maintain overall functionality of cellular proteomes. Data accumulated over decades demonstrate that the effectiveness of elements of the proteostasis network declines with age. In this scenario, failure to degrade misfolded or faulty proteins increases the risk of protein aggregation, chronic inflammation, and the development of age-related diseases. This is especially important in the context of aging-related modification of functions of the immune system.